Eclipse Bay - Krentz, Jayne Ann (Jove Books, 2000)
Death and desire walk hand in hand in the tiny town of Eclipse Bay, located along the rocky coast of Oregon. The steep cliffs and crashing waves are no less hazardous than the nasty secrets that many in town keep. And at the heart of it all is the generations-long rivalry and hostilities between two families: the Hartes and the Madisons. The two families have waged a bitter battle ever since the elder men in the family became business partners years ago and were then torn apart over a beautiful but unscrupulous woman. Now, the Hartes are part of the upper crust in Eclipse Bay whereas the Madisons are known for being womanizing scallywags who are in trouble more than they are out. Everyone assumes Hannah Harte will go on to great personal success and a solid, well-positioned marriage. But the expectations for Rafe Madison include a life of trouble and the likelihood of jail time. But fate, and a chance encounter on a deserted beach late one night, changes everything. Rafe Madison is accused of murdering the young girl he was dating, who abandoned him out on the beach. Hannah, also abandoned by her date after she fought off his amorous advances, finds herself in the position of being Rafe Madison's alibi. Though Hannah does the right thing by telling the truth about Rafe, she pays for it when rumors about the true nature of their chance encounter start to circulate.